2019
DOI: 10.1101/511147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial Diversity in Feces of Wild Bald Eagles, Turkey Vultures and Common Ravens from the Pacific Northwest Coast, U.S.A

Abstract: RC) 28 29 30 ¶ These authors contributed equally to this work. 2 31 Abstract 32Birds harbor diverse microorganisms in their guts, which collectively fulfill important 33 roles in providing their hosts with nutrition and protection from pathogens. Although numerous 34 studies have investigated the presence of certain pathogenic bacteria in the feces of wild birds, 35 only a few have attempted to investigate the microbiota of the gut. This study analyzed the avian 36 bacteria present in the cloaca of avian scave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Proteobacteria and Firmicutes have also been identified as abundant bacteria in other microbiome studies of avian tick ectoparasites [46], carrion beetles [47], as well as other birds [44,48]. Similarly, 80% of the bacterial sequences detected from cloacal swabs of Bald Eagles captured from the coastal beaches of Washington and Oregon, were Firmicutes and Proteobacteria [49], suggesting these prominent phyla can be found across a range of host species (e.g., from insects to birds).…”
Section: Discussionmentioning
confidence: 83%
“…Proteobacteria and Firmicutes have also been identified as abundant bacteria in other microbiome studies of avian tick ectoparasites [46], carrion beetles [47], as well as other birds [44,48]. Similarly, 80% of the bacterial sequences detected from cloacal swabs of Bald Eagles captured from the coastal beaches of Washington and Oregon, were Firmicutes and Proteobacteria [49], suggesting these prominent phyla can be found across a range of host species (e.g., from insects to birds).…”
Section: Discussionmentioning
confidence: 83%
“…2018, Crespo et al . 2019). These studies showed that the skin microbiome was in general more diverse and had a different microbial composition compared with the intestinal microbiome, which is more specialized and less diverse (Roggenbuck et al .…”
Section: Resultsmentioning
confidence: 99%